2022
DOI: 10.1177/0734242x221122560
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the influence of combined particle size pretreatment and Fe3O4 additive on fuel yields of Arachis Hypogea shells

Abstract: A smart energy recovery process can achieve maximum energy recovery from organic wastes. Pretreatment of feedstock is essential to biogas and methane yields during the anaerobic digestion process. This work combined particle size reduction with Fe3O4 nanoparticles to investigate their influence on biogas and methane yields from anaerobic digestion of Arachis hypogea shells. Twenty milligrams per litre of Fe3O4 nanoparticles was implemented with 2, 4, 6 and 8 mm particle sizes and a single treatment of Fe3O4 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Flush gas for carbon dioxide removal was set at 10%, stirring time was set at 60 s and 60 s off time, and the mixer speed of 80% was maintained throughout the digestion process. Methane yield was predicted to be 60% [27], and a headspace of 100 mL was maintained for all digesters. The anaerobic condition was set in the digester when nitrogen gas purged oxygen off the system before connecting the silicon pipes to the digester.…”
Section: Methodsmentioning
confidence: 99%
“…Flush gas for carbon dioxide removal was set at 10%, stirring time was set at 60 s and 60 s off time, and the mixer speed of 80% was maintained throughout the digestion process. Methane yield was predicted to be 60% [27], and a headspace of 100 mL was maintained for all digesters. The anaerobic condition was set in the digester when nitrogen gas purged oxygen off the system before connecting the silicon pipes to the digester.…”
Section: Methodsmentioning
confidence: 99%
“…Multidisciplinary studies in nanomaterials science and technology have established that nanoparticles can revolutionize the structural arrangement of biogas feedstocks and enhance the methanogenic bacteria. 136 The enzymes’ catalytic activities can be improved by using nanoscale materials that can immobilize the enzymes, and they are called nanocatalysts. 137 The enzyme immobilization with the application of cross-linking molecules produces a spacer that minimizes stiff impediments between the solid base and enzyme, improving the flexibility of immobilized enzymes.…”
Section: Macroalgae Pretreatmentmentioning
confidence: 99%
“…Fe nanoparticles as nano additives have been observed to efficiently lower the amount of H 2 S in the gas yield, enhance methane yield, and reduce the lag period in some situations. 136,142 Fe 2 O 3 's direct interspecies electron transfer capabilities have the potential to significantly enhance the anaerobic digestion process’ methanogenesis step. The majority of the reduced electron carriers is thought to be transformed into carbon dioxide, while the syntrophy route and methanogen electron exchange are thought to constitute interspecies electron transfers.…”
Section: Macroalgae Pretreatmentmentioning
confidence: 99%
“…The pressure drop was used to calculate the jet velocity W in the resonant chamber of the device. According to the data obtained, the change in the mean square oscillation amplitude p/q reduced to the velocity head (q = ρ • W 2 /2) on the jet velocity was studied, similarly to [56].…”
Section: Goal and Scopementioning
confidence: 99%
“…The reaction system is flexible in scale and can be applied in the field of edible oil refining, algae oil extraction, renewable fuel production, biodiesel production, etc. A number of studies have shown that with a decrease in the particle size of the raw material supplied to the digester, the yield of biogas increases [56,[60][61][62][63]. An increase in the surface area of the organic material provides a larger contact area for microorganisms, which leads to an intensification of the gas formation process [63].…”
Section: P R =mentioning
confidence: 99%